2017
DOI: 10.1111/1462-2920.13871
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GntR as regulator of the glucose metabolism in Pseudomonas aeruginosa

Abstract: In contrast to Escherichia coli, glucose metabolism in pseudomonads occurs exclusively through the Entner-Doudoroff (ED) pathway. This pathway, as well as the three routes to generate the initial ED pathway substrate, 6-phosphogluconate, is regulated by the PtxS, HexR and GtrS/GltR systems. With GntR (PA2320) we report here the identification of an additional regulator in Pseudomonas aeruginosa PAO1. GntR repressed its own expression as well as that of the GntP gluconate permease. In contrast to PtxS and GtrS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
(74 reference statements)
0
27
0
1
Order By: Relevance
“…As has been mentioned by Daddaoua et al . (), the inspection of the genetic context of genes involved in glucose metabolism in P. aeruginosa resulted in the detection of a GntR‐like transcriptional regulator (Jain, ), that is predicted to possess an N‐terminal HTH DNA‐binding motif and a periplasmic binding protein‐like domain for effector binding (Daddaoua et al ., ). In P. aeruginosa , it was found that the gntR gene is transcribed divergently to the gnuK gene (gluconokinase), which is located adjacent to those of the gluconate transporter (GntP) and a glyceraldehyde‐3‐phosphate dehydrogenase (GapN) (Fig.…”
Section: Transcriptional Regulators Involved In Pseudomonas Carbohydrmentioning
confidence: 99%
See 3 more Smart Citations
“…As has been mentioned by Daddaoua et al . (), the inspection of the genetic context of genes involved in glucose metabolism in P. aeruginosa resulted in the detection of a GntR‐like transcriptional regulator (Jain, ), that is predicted to possess an N‐terminal HTH DNA‐binding motif and a periplasmic binding protein‐like domain for effector binding (Daddaoua et al ., ). In P. aeruginosa , it was found that the gntR gene is transcribed divergently to the gnuK gene (gluconokinase), which is located adjacent to those of the gluconate transporter (GntP) and a glyceraldehyde‐3‐phosphate dehydrogenase (GapN) (Fig.…”
Section: Transcriptional Regulators Involved In Pseudomonas Carbohydrmentioning
confidence: 99%
“…In P. aeruginosa, it was found that the gntR gene is transcribed divergently to the gnuK gene (gluconokinase), which is located adjacent to those of the gluconate transporter (GntP) and a glyceraldehyde-3-phosphate dehydrogenase (GapN) (Fig. 2) It has been proposed that GntR regulates its own expression, as well as that of a gluconokinase (GnuK), gluconate permease (GntP) and gluconate 6phosphate dehydrogenase (GntZ) gene (Daddaoua et al, 2017;Del Castillo et al, 2007).…”
Section: Ocs Involved In Carbohydrate Catabolism Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Lon negatively regulated the gluconate kinase activity by binding to the gntR promoter in KB Based on the ChIP-seq results, we performed an EMSA and verified the direct interaction between Lon and the promoter of gntR (−95 to +55 from ATG), which encodes a transcriptional repressor involved in glucose metabolism ( Fig. 4H; Daddaoua et al, 2017;Udaondo et al, 2018). In KB, the expression level of gntR was approximately twofold lower in the Δlon strain than in the WT, whereas no significant difference was observed in MM ( Fig.…”
Section: Lon Positively Regulated Bacterial Motility By Binding Direcmentioning
confidence: 95%